Fate of fatty acids derived from biogas residues in arable soil. (December 2015) - Coban, H.; Miltner, A.; Kästner, M.
Abstract: Biogas residues are rich in microbial biomass and contribute to organic matter formation when applied to soils. Here we present a detailed analysis of the fatty acids derived from 13 C-labelled biogas residues applied to arable soil and incubated for 378 days. We applied a differential approach using phospholipid fatty acids and total fatty acids to evaluate the carbon dynamics in living biomass and non-living soil organic matter. Biogas residue addition increased the microbial biomass in soil. The sum of 13 C-labelled phospholipid fatty acids decreased to ∼60% during incubation whereas the decrease of t-FA was higher (to 33%). Compound-specific fatty acid analysis showed fatty acid specific incorporation or loss of 13 C, indicating hints for the carbon flow within the microbial food web. Overall, microbial biomass in biogas residues may be a significant contributor to soil organic matter formation. Highlights: Fate of fatty acids derived from biogas residues was traced in soil. The decrease of 13 C in total fatty acids was higher than that in phospholipid fatty acids. The loss or gain of 13 C was specific for individual fatty acids. Microbial biomass in biogas residues may be a significant contributor to soil organic matter formation.